Shock demagnetization in an ambient magnetic field at the Dhala impact structure, India - Pandey, Ambrish Kumar; Agarwal, Amar; Joshi, Gaurav; Sangode, Satish; Venkateshwarlu, Mamilla (Communications Earth & Environment, 2026)
Impact-generated shock waves can modify the remanent magnetization preserved in target rocks, yet their effects remain poorly constrained. Here we examine how shock waves modify rock magnetization by analysing unshocked granitoids and diorites, and shock-affected monomict breccia and impact melt rock of the Paleoproterozoic Dhala impact structure in India. Microscopic, thermomagnetic and hysteresis analyses were used to identify magnetic minerals and their domain states. Remanent magnetization and demagnetization experiments were performed to evaluate shock effects on the palaeomagnetic behaviour of impact-generated and unshocked target rocks. The unshocked rocks contain strong and stable magnetization carried by titanomagnetite. In contrast, the monomict breccia carries titanomagnetite and titanohematite and shows extremely weak and unstable magnetization, consistent with shock-related grain-size reduction and microfracturing. Impact melt rocks display intermediate behaviour, with titanomagnetite, titanohematite and pyrrhotite as magnetic carriers. These results show that shock can substantially reduce crustal magnetization. The results help to explain weak magnetic signatures at terrestrial and planetary impact structures, even in the presence of an ambient magnetic field.